FUNCTIONS OF THE VILLAGE DEVELOPMENTAL BOARD (BPD) ACCORDING TO LAW NUMBER 6 OF 2014 AND IMPLEMENTATION IN PURAKA I VILLAGE SEI LEPAN DISTRICT, LANGKAT DISTRICT - Mhd. Iqbal Ajmi Lubis; Tamaulina Br Sembiring (RADJA PUBLIKA, 2024)
The Village Consultative Body (BPD) is an institution that carries out village government functions whose members are representatives of the village population based on regional representation and are determined democratically. In the village government system, village government will run effectively if the elements or institutions administering village government can run well. The Village Consultative Body (BPD) is an institution that embodies democracy in the administration of village government. BPD members are representatives of the population of the village concerned based on regional representation. In general, those selected to be members of the BPD consist of the chairman of the Rukun Warga, traditional leaders, professional groups, religious leaders and other figures or community leaders. It can be concluded that the function of the Village Consultative Body (BPD) is to discuss and approve Draft Village Regulations, accommodate community aspirations, and supervise the performance of the Village Head. Based on the research results, it shows that the function in making regulations is more implemented and realized, which is different from the function in accommodating community aspirations and supervising the performance of the Village Head, which has not been optimal in its implementation due to the lack of understanding of BPD members regarding their duties and functions based on applicable regulations.